Home alone: a systematic review and meta‐analysis on the effects of individual housing on body weight, food intake and visceral fat mass in rodents. (15th January 2018) - Schipper, L.; Harvey, L.; van der Beek, E. M.; van Dijk, G.
Summary: Rats and mice are widely used to study environmental effects on psychological and metabolic health. Study designs differ widely and are often characterized by varying (social) housing conditions. In itself, housing has a profound influence on physiology and behaviour of rodents, affecting energy balance and sustainable metabolic health. However, evidence for potential long‐term consequences of individual versus social housing on body weight and metabolic phenotype is inconsistent. We conducted a systematic literature review and meta‐analyses assessing effects of individual versus social housing of rats and mice, living under well‐accepted laboratory conditions, on measures of metabolic health, including body weight, food intake and visceral adipose tissue mass. Seventy‐one studies were included in this review; 59 were included in the meta‐analysis. Whilst housing did not affect body weight, both food intake and visceral adipose tissue mass were significantly higher in individually compared with socially housed animals. A combination of emotional stress and lack of social thermoregulation likely contributed to these effects. Increased awareness of consequences and improved specifications of housing conditions are necessary to accurately evaluate efficacy of drugs, diets or other interventions on metabolic and other health outcomes because housing conditions are rarely considered as possible moderators of reported outcomes.